Issues of Providing Transport Services to Sparsely Populated Areas: A Case Study of the Territory of the National Park Šumava in the Czech Republic - Heřmánková, Andrea; Kleprlík, Jaroslav (My University, 2024)
This paper deals with public transport services in sparsely populated areas. The definition of the term transport services and possible approaches to its provision is given in the introduction. The term sparsely populated area is subsequently defined. The problems that arise during the organization of transport services in these areas are further defined. These problems lie primarily in the variations in the number of people in the thousands in the area in the off-tourist season and in the summer tourist season. This affects the organization of transport and the organization of transport services. This paper proposes the technological procedure and measures for improving transport services in sparsely populated areas outside and during the summer tourist season. The proposals are applied in a selected sparsely populated area in the territory of the National Park Šumava and the Šumava Protected Landscape Area in the Czech Republic.
Problémy se zajišťováním dopravní obslužnosti v řídce osídlených oblastech: Případová studie území Národního parku Šumava v České republice
Keywords: transport services; sparsely populated areas; periphery; border areas; tourist areas; dopravní obslužnost; řídce osídlená oblast; periferie; příhraniční oblasti; turistické oblasti